40 Years of Japanese Contemporary Art : 10th Anniversary of New Building. - Otoba, Satoshi (Tokyo : Tokyo Metropolitan Art Museum, 1985)
Matsumoto, Shunsuke ; Ai-Mitsu ; Tsuruoka, Masao ; Aso, Saburo ; Maruki, Iri ; Maruki, Toshi ; Sugimata, Tadashi ; Kitawaki, Noboru ; Abe, Nobuya ; Hamada, Chimei ; Ay-O ; Ikeda, Masuo ; Nakamura, Hiroshi ; Kazuki, Yasuo ; Horiuchi, Masakazu ; Tatehata, Kakuzo ; etc.
40 Years of Japanese Contemporary Art : 10th Anniversary of New Building, Tokyo Metropolitan Art Museum, Tokyo, October 12 - December 8, 1985
English-Japanese
kunstcatalogus
Keywords: Japan